Altered Outer Hair Cell Mitochondrial and Subsurface Cisternae Connectomics Are Candidate Mechanisms for Hearing Loss in Mice - Perkins, Guy (J Neurosci, 2020)
Organelle crosstalk is vital for cellular functions. The propinquity of mitochondria, ER, and plasma membrane promote regulation of multiple functions, which include intracellular Ca(2+) flux, and cellular biogenesis. Although the purposes of apposing mitochondria and ER have been described, an understanding of altered organelle connectomics related to disease states is emerging. Since inner ear outer hair cell (OHC) degeneration is a common trait of age-related hearing loss, the objective of this study was to investigate whether the structural and functional coupling of mitochondria with subsurface cisternae (SSC) was affected by aging. We applied functional and structural probes to equal numbers of male and female mice with a hearing phenotype akin to human aging. We discovered the polarization of cristae and crista junctions in mitochondria tethered to the SSC in OHCs. Aging was associated with SSC stress and decoupling of mitochondria with the SSC, mitochondrial fission/fusion imbalance, a remarkable reduction in mitochondrial and cytoplasmic Ca(2+) levels, reduced K(+)-induced Ca(2+) uptake, and marked plasticity of cristae membranes. A model of structure-based ATP production predicts profound energy stress in older OHCs. This report provides data suggesting that altered membrane organelle connectomics may result in progressive hearing loss.